Utilization of Moringa, Tiwul and Catfish Leaves as Ingredients for Making Food to Prevent Stunting - Triwik Sri Mulati; Susilo Wirawan; Titik Lestari; Dyah Noviawati Setya Arum; Sri Wahyuni; Lutfiana Puspita Sari; Yuniar Indo Masadi; Muftikha Khoiri Rahmawati; Lilis Setyaningsih; Dina Fadhilah (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Sambirejo Village is one of the stunting locus areas. Based on 2022 data, there are 23 children under two years old who are stunted out of a total of 192 people, and 50 children under five years old who are stunted out of a total of 494 toddlers. One of the causes of stunting is based on maternal anemia and CED (Chronic Energy Deficiency). In 2022, data was obtained from 83 pregnant women, there were 43 people experiencing anemia and 15 people with KEK. The incidence of anemia in adolescent girls was 45 and KEK was 58 out of a total of 361 adolescent girls. If this condition is not prevented, the incidence of anemia, CED and stunting will continue to increase from year to year. Alternative food to increase iron and prevent CED to prevent stunting is to use food ingredients taken from local wisdom in the form of processed food using three basic triad ingredients (moringa leaves, catfish and tiwul/cassava) in the form of: cilok catfish, moringa ice cream and chips / cassava-catfish sticks which have nutritional and economic value. Through this training, 100 target participants were given health material and demonstrations on making highly nutritious food preparations. The results of this activity prove that there is an increase in knowledge about anemia, CED, stunting and skills in making processed food that has nutritional value and marketability.